Flux-assisted polytypism in the [Na2Cl]GaQ2 heterolayered salt-inclusion chalcogenide family. Issue 15 (27th March 2023) - Berseneva, Anna A.; Klepov, Vladislav V.; Tisdale, Hunter B.; zur Loye, Hans-Conrad
Abstract : Via flux-assisted synthesis, we discovered three novel salt-inclusion materials, t -[Na2 Cl]GaS2, o -[Na2 Cl0.9 I0.1 ]GaSe2, and t -[Na2 Cl0.9 I0.1 ]GaSe2, and two new selenides, Na2 GaSe3 and Na4 Ga2 Se5, by changing the flux from NaCl/NaI to NaBr/NaI, respectively. Abstract : Two polytypic heterolayered salt-inclusion chalcogenides, o -[Na2 Cl]GaQ2 and t -[Na2 Cl]GaQ2, were obtained via a NaCl/NaI flux-assisted synthesis, as part of an investigation of the Na–Ga–Q (Q = S and Se) system. The use of a different flux, NaBr/NaI, in the Na–Ga–Se system did not lead to the formation of salt-inclusion phases, but instead the novel Na2 GaSe3 and Na4 Ga2 Se5 phases were obtained. Thermal and electronic properties of [Na2 Cl]GaS2 materials were investigated with differential scanning calorimetry, post-quenching ex situ powder X-ray diffraction (PXRD), high-temperature PXRD, and enthalpy and electronic structure calculations via density functional theory. Those studies determined the absence of any temperature-induced phase transition between the o -[Na2 Cl]GaS2 and t -[Na2 Cl]GaS2 polytypic compounds. Moreover, we probed the suitability of the heterolayered [Na2 Cl]GaS2 single crystals as a sorbent for UO2 2+ uptake and monitored this process by energy-dispersive and infrared spectroscopies and PXRD, which revealed that the [Na2 Cl] + insert could be exchanged with UO2 2+ on the surface while the UO2 2+ intercalation decomposes the [Na2 Cl]GaS2 structure.